1999
DOI: 10.1126/science.284.5421.1811
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Spine Delivery and Redistribution of AMPA Receptors After Synaptic NMDA Receptor Activation

Abstract: To monitor changes in alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionate (AMPA) receptor distribution in living neurons, the AMPA receptor subunit GluR1 was tagged with green fluorescent protein (GFP). This protein (GluR1-GFP) was functional and was transiently expressed in hippocampal CA1 neurons. In dendrites visualized with two-photon laser scanning microscopy or electron microscopy, most of the GluR1-GFP was intracellular, mimicking endogenous GluR1 distribution. Tetanic synaptic stimulation induced a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
798
3
8

Year Published

2000
2000
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,173 publications
(858 citation statements)
references
References 35 publications
49
798
3
8
Order By: Relevance
“…Previous studies found no detectable changes in the VTA in total cellular protein levels of GluR1 between cocaine-and saline-treated mice (Ungless et al, 2001). However, because hippocampal LTP is dependent on the insertion of GluR1 into the postsynaptic membrane at synapses (Shi et al, 1999) rather than a simple increase in total cellular GluR1 levels, we reasoned that increases in AMPA receptor number at the surface might not be reflected in total cellular protein levels but only in surface receptor expression. Therefore, we examined surface expression of AMPA and NMDA receptors on VTA neurons from rats that had received a single dose of either saline or amphetamine 24 h earlier.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Previous studies found no detectable changes in the VTA in total cellular protein levels of GluR1 between cocaine-and saline-treated mice (Ungless et al, 2001). However, because hippocampal LTP is dependent on the insertion of GluR1 into the postsynaptic membrane at synapses (Shi et al, 1999) rather than a simple increase in total cellular GluR1 levels, we reasoned that increases in AMPA receptor number at the surface might not be reflected in total cellular protein levels but only in surface receptor expression. Therefore, we examined surface expression of AMPA and NMDA receptors on VTA neurons from rats that had received a single dose of either saline or amphetamine 24 h earlier.…”
Section: Resultsmentioning
confidence: 77%
“…In the hippocampus, LTP is dependent on increased insertion of the AMPA receptor subunit, GluR1 (Shi et al, 1999;Zamanillo et al, 1999). Previous studies found no detectable changes in the VTA in total cellular protein levels of GluR1 between cocaine-and saline-treated mice (Ungless et al, 2001).…”
Section: Resultsmentioning
confidence: 95%
“…Both results were blocked by NMDAR antagonists and postsynaptically applied tetanus toxin. In organotypic slice cultures overexpressing GluR1, activation of NMDARs was sufficient to translocate this subunit into spines 30 and drive the synaptic insertion of AMPARs made exclusively of GluR1 subunits. It was found that perfusion of neurons with activated Ca 2+ -calmodulin kinase type II (CaMKII) was sufficient to drive receptor insertion.…”
Section: Insertion Of Amparsmentioning
confidence: 99%
“…46 ) incorporated into postsynaptic membrane organelles, it was shown that high-frequency stimulation similar to the kind used to induce LTP led to Ca 2+ -dependent exocytosis. Evidence that this postsynaptic exocytosis delivers AMPARs comes from experiments in which transfection of CA1 neurons in organotypic slice cultures with a green fluorescent protein (GFP)-GluR1 fusion protein and application of an LTP induction protocol triggers the translocation of this protein from dendritic shafts to the spines 30 . Using rectification as an electrophysiological tag, the authors could show that GluR1 homomeric receptors were indeed synaptically inserted 47 .…”
Section: Do Ampars Move During Synaptic Plasticity? Ltpmentioning
confidence: 99%
“…8,9 However, the highest efficiency reported so far is 13.5%, 8 far less than other methods such as viral infection, which often reaches more than 40% of transduction efficiency. 10,11 To increase the transfection rate while maintaining low toxicity is the ultimate goal for every gene transfer method. The low efficiency of Ca 2+ -phosphate transfection has significantly limited its applications, such as in biochemical and electrophysiological analyses of gene functions.…”
Section: Introductionmentioning
confidence: 99%